Implementasi Restorative Justice melalui Sanksi Adat Jambar dan Tajuak dalam Penanggulangan Pencemaran Nama Baik di Era Digital: Studi Kasus di Desa Pasar Talo, Kabupaten Seluma - Bella Ananda Sari; Selpa Rosalenda; Elia Setri; Uci Febriani; Mardhatillah (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2026)
This empirical juridical research analyzes the effectiveness of the traditional sanctions Jambar and Tajuak in addressing digital defamation in Pasar Talo Village, Seluma Regency. Although national criminal law dominates the formal legal framework, the local community continues to maintain customary mechanisms for resolving disputes. The deliberation process led by traditional elders (tuha-tuha adat) at the customary hall prioritizes restoring social relationships, protecting the dignity of the injured party and achieving reconciliation. This mechanism is considered more responsive to community needs than formal litigation. Despite challenges posed by social media’s cross-regional and anonymous nature, customary values remain relevant as instruments for conflict resolution and maintaining social balance in the digital era.